Prevalence of internalized stigma in patients with psychiatric illness in Abha, Southern Region, Saudi Arabia - Abdulmajeed A Zarbah; Hayfa A Al Alfard; Hassan S Alamri; Nada Al Edrees; Nouf S Alshahrani; Ali F Alshehri (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Mental stigma occurs when patients with various mental disorders are labeled by their disorders. Little is known about the burden of mental stigma on patients with mental disorders. The aim of this study was to evaluate the incidence of mental stigma on patients with psychiatric disorder in Saudi Arabia. MATERIALS AND METHODS: This cross-sectional study was conducted among previously diagnosed patients with any psychiatric disorder attending King Khalid Hospital, Abha, Saudi Arabia. The patients were interviewed with a sociodemographic questionnaire and a validated Arabic version of the Internalized Stigma of Mental Illness (ISMI-29) scale. Chi-square test and t-test were used to assess the association between various demographic characteristics and presence of stigma. RESULTS: The study included 489 patients with different psychiatric disorders. The mean age of the participants was 32.8 years and 54.6% were females. About 39% participants showed no to minimal internalized stigma, 37.4% of total sample had mild stigma, 20% had moderate stigma, and 3.7% had severe stigma. A signficantly higher proportion (71.4%) of widowed patients had stigma (P = 0.032). CONCLUSION: Self-stigma is prevalent among patients with psychiatric disorders in Abha, Saudi Arabia, but lower than the prevalence in developing countries. Marital status has a significant impact on the prevalence and severity of the self-stigma of patients. There is a need for awareness program to reduce self-stigma. Psychiatric institutions should also focus on promotion of patients' social life and increase patient's awareness of certain issues that could prevent stigma.